A Case of Painful Legs and Moving Toes Syndrome in a Young Woman - Bae, Hyoeun; Shin, Dae-seop; Kang, Mi-kyoung; Lee, Hyun Chang; Jung, Ki-Young (Journal of sleep medicine, 2022)
Painful legs and moving toes syndrome (PLMT) is a rare syndrome characterized by pain in the lower extremities and involuntary movements of single or multiple toes. A 29-year-old woman with lumbosacral intervertebral disc herniation complained of bilateral foot pain and involuntary toe movements for three months. This is the first case of PLMT in a young adult patient with a lumbosacral intervertebral disc herniation in Korea.